Immunogenicity and protective efficacy of GBP510/AS03 vaccine against SARS-CoV-2 delta challenge in rhesus macaques - Catherine Jacob-Dolan; Jingyou Yu; Katherine McMahan; Victoria Giffin; Abishek Chandrashekar; Amanda J. Martinot; Tochi Anioke; Olivia C. Powers; Kevin Hall; David Hope; Jessica Miller; Nichole P. Hachmann; et al. (npj Vaccines, 2023)
Abstract Despite the availability of several effective SARS-CoV-2 vaccines, additional vaccines will be required for optimal global vaccination. In this study, we investigate the immunogenicity and protective efficacy of the GBP510 protein subunit vaccine adjuvanted with AS03, which has recently been authorized for marketing in South Korea under the trade name SKYCovioneTM. The antigen in GBP510/AS03 is a two-part recombinant nanoparticle, which displays 60 receptor binding domain (RBD) proteins of SARS-CoV-2 Spike on its surface. In this study we show that GBP510/AS03 induced robust immune responses in rhesus macaques and protected against a high-dose SARS-CoV-2 Delta challenge. We vaccinated macaques with two or three doses of GBP510/AS03 matched to the ancestral Wuhan strain of SARS-CoV-2 or with two doses of GBP510/AS03 matched to the ancestral strain and one dose matched to the Beta strain. Following the challenge with Delta, the vaccinated macaques rapidly controlled the virus in bronchoalveolar lavage and nasal swabs. Binding and neutralizing antibody responses prior to challenge correlated with protection against viral replication postchallenge. These data are consistent with data with this vaccine from the phase 3 clinical trial.